Optimizing odor identification testing as quick and accurate diagnostic tool for Parkinson's disease. Issue 9 (9th May 2016) - Mahlknecht, Philipp; Pechlaner, Raimund; Boesveldt, Sanne; Volc, Dieter; Pinter, Bernardette; Reiter, Eva; Müller, Christoph; Krismer, Florian; Berendse, Henk W.; van Hilten, Jacobus J.; Wuschitz, Albert; Schimetta, Wolfgang; et al.
ABSTRACT: Introduction: The aim of this study was to evaluate odor identification testing as a quick, cheap, and reliable tool to identify PD. Methods: Odor identification with the 16‐item Sniffin' Sticks test (SS‐16) was assessed in a total of 646 PD patients and 606 controls from three European centers (A, B, and C), as well as 75 patients with atypical parkinsonism or essential tremor and in a prospective cohort of 24 patients with idiopathic rapid eye movement sleep behavior disorder (center A). Reduced odor sets most discriminative for PD were determined in a discovery cohort derived from a random split of PD patients and controls from center A using L1‐regularized logistic regression. Diagnostic accuracy was assessed in the rest of the patients/controls as validation cohorts. Results: Olfactory performance was lower in PD patients compared with controls and non‐PD patients in all cohorts (each P < 0.001). Both the full SS‐16 and a subscore of the top eight discriminating odors (SS‐8) were associated with an excellent discrimination of PD from controls (areas under the curve ≥0.90; sensitivities ≥83.3%; specificities ≥82.0%) and from non‐PD patients (areas under the curve ≥0.91; sensitivities ≥84.1%; specificities ≥84.0%) in all cohorts. This remained unchanged when patients with >3 years of disease duration were excluded from analysis. All 8 incident PD cases among patients with idiopathic rapid eye movement sleep behavior disorder were predicted with the SS‐16 and the SS‐8 (sensitivity, 100%; positive predictive value, 61.5%). Conclusions: Odor identification testing provides excellent diagnostic accuracy in the distinction of PD patients from controls and diagnostic mimics. A reduced set of eight odors could be used as a quick tool in the workup of patients presenting with parkinsonism and for PD risk indication. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society